2015
DOI: 10.1002/sca.21281
|View full text |Cite
|
Sign up to set email alerts
|

Formation of protective deposits by anti‐erosive toothpastes—A microscopic study on enamel with artificial defects

Abstract: This study investigated formation of protective deposits on the enamel surface after application of several anti-erosive toothpastes with different active ingredients. NaF-containing Sensodyne Pronamel, SnCl /F-based Elmex Erosion Protection and calcium phosphate-based BioRepair Plus Sensitivity Control, SensiShield and Enamel Care toothpastes with claimed anti-erosive properties were tested. Artificial saliva and Elmex Erosion Protection mouth rinse served as control groups. The toothpastes were applied 30 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Two studies did not realize the intervention group ( Austin et al, 2014 ; Passos, Rodrigues & Santiago, 2018 ), and three evaluated primary teeth ( Elwardani, Harhash & Zaky, 2019 ; Maden et al, 2017 ; Rallan et al, 2013 ), conflicting with the previously established eligibility criteria. Finally, four studies were selected in this systematic review according to the eligibility criteria ( Bradna et al, 2015 ; João Souza et al., 2017 ; Panich & Poolthong, 2009 ; Ranjitkar et al, 2009 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not realize the intervention group ( Austin et al, 2014 ; Passos, Rodrigues & Santiago, 2018 ), and three evaluated primary teeth ( Elwardani, Harhash & Zaky, 2019 ; Maden et al, 2017 ; Rallan et al, 2013 ), conflicting with the previously established eligibility criteria. Finally, four studies were selected in this systematic review according to the eligibility criteria ( Bradna et al, 2015 ; João Souza et al., 2017 ; Panich & Poolthong, 2009 ; Ranjitkar et al, 2009 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The significant increase in Ra observed after APF treatment (Figure ) can be attributed to the precipitation of deposits formed by the fluoride treatments (CaF 2 ‐like cubes precipitate), which remained after erosion (Rošin‐Grget & Linčir, ). The mechanism of action of conventional fluoride products can explain this deposition, which increases surface roughness because the fluoride ions form fluoridated apatites in the enamel structure and accelerate the deposition of CaF 2 ‐like material and calcium phosphates (CaPs) from the supersaturated saliva (Bradna, Vrbova, Fialova, Housova, & Gojisova, ; Cate, ; Ten Cate & Featherstone, ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of toothpastes and mouthwashes containing hydroxyapatite microclusters in promoting the deposition of a carbonate-hydroxyapatite particle coating on eroded enamel has already been under investigation in vitro [ 17 , 18 ]. However, uncertainty remains about the sustainability of such mineral deposits and there is sparse evidence for the efficacy of this approach in vivo or in situ [ 19 ]. Furthermore it has been suggested that the addition of hydroxyapatite nanoparticles to an erosive soft drink significantly decreases its erosive potential by providing a calcium and phosphate supersaturation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%